Effect of the nanostructured carbon sorbent «Ingo-2» and cadmium chloride on limfodynamic and composition of lymph - Tuleuhanov, S. T.; Ablayhanova, N. T.; Sharipova, S. A.; Dinistanova, B. K.; Mansurov, Z. A. (International Journal of Biology and Chemistry, 2012)
The effect of cadmium ions and nanostructured carbon sorbent on limfodynamic and composition of lymph was stadies. The experiments showed that prolonged poisoning of rats with cadmium chloride (per os) causes changes of biochemical composition and physic-chemical parameters of lymph and blood plasma. The accumulation was marked by of cadmium ions in the lymph nodes, where their concentration is increased 5-7 times of the original level. Using n nanostructured carbon sorbent «Ingo-2» reduces substantially negative effect of cadmium on limfodynamic and indicators of lymph.